2013
DOI: 10.1007/s00170-013-4817-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the performance of coated and uncoated carbide tools in drilling thick CFRP/aluminium alloy stacks

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. A scanning electron microscope (SEM) and a numerical microscope, provided with a scanning device, were periodically used to analyse tool wear mechanisms and to measure wear progression of the tool cutting edges. For both coated and uncoated drills, abrasion was the dominant tool wear mechanism, affecting the entire cutting edges. Higher wear was observed on unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…The phenomenon was also observed by Montoya et al. 11 It can be attributed to the increased tool instability when drilling the bottom Al layer. With a spindle speed of 1000 rpm, (see Fig.…”
Section: Hole Diametermentioning
confidence: 54%
See 2 more Smart Citations
“…The phenomenon was also observed by Montoya et al. 11 It can be attributed to the increased tool instability when drilling the bottom Al layer. With a spindle speed of 1000 rpm, (see Fig.…”
Section: Hole Diametermentioning
confidence: 54%
“…2,10 Cavities, micro cracks and matrix resin degradation on the hole surface of CFRP were observed by Xu et el. 5 during drilling of T800S/250F CFRP laminates and Montoya et al 11 during drilling of CFRP/Al stacks which was closely related to the too high drilling temperature.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Qi et al [13] established the relation of layers and critical axial force in the CFRP/Metal drilling based on linear elastic fracture mechanics, and used the relation with axial force to predict the layer defects in CFRP drilling. Montoya et al [14] analyzed the influences on the cutting force, hole quality, and tool wear when using coated or uncoated carbide cutters to drill CFRP/Al. Brinksmeier et al [15] studied the lamination drilling of Al/CFRP/Ti and proposed a new method to drill multiple layers by step drill.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed when the drill tip initially contacted surface on the titanium after machining of CFRP with changing cutting parameters, it could significantly improve the quality and tool life. Montoya et al [9] found abrasion was the dominant tool wear pattern and measured wear progression of the cutting edges when drilling of CFRP/Al stacks using tungsten carbide drills.…”
Section: Introductionmentioning
confidence: 99%